Polycyclic Aromatic Hydrocarbons in Petroleum Sludge Cake: Extraction and Origin - A Case Study - Pakpahan, E.N. (Centre for Promoting Ideas (CPI), USA, 2011)
The aim of this study was to determine the most effective solvent(s) of Acetone, Dichloromethane (DCM), n-Hexane solvents and their mixtures of PAH soxhlet extraction (SE) from petroleum sludge cake sample; also to determine the origin of PAH in petroleum sludge cake sample - a case study. Gas chromatograph-mass spectroscopy (GC-MS) was used for analytical determination of the selected PAH compounds. The result was revealed that the binary mixture solvent of Acetone+n-Hexane (1:1) (v/v) was the most effective of solvent common used because it was the only one which was able to extract the selected PAH compounds and yielded the highest amount of total selected PAH extracted from the petroleum sludge cake. Meanwhile, n-Hexane solvent and DCM+n-Hexane (1:1) were less effective ones. The quantitative result of analysis of selected PAH compounds: Phenanthrene/Ph, Anthracene/An (both 3-rings) and Fluoranthene/Fl, Pyrene/Py (both 4-rings) could be used to determine the origin of PAH. In conjunction with their molecular ratio: An/(An+Ph) of 0.045, and Fl/(Fl+Py) of 0.483, cross-plotting of An/(An+Ph) vs Fl/(Fl+Py) indicated that the PAHs compounds in petroleum sludge cake samples originated dominantly from pyrolytic (petroleum combusted) sources.